Tingkat Kecemasan Mahasiswa Tingkat Akhir Dalam Menghadapi Tugas Akhir Karya Tulis Ilmiah (KTI) Di Akademi Keperawatan Yapenas 21 Maros - Nurmasita, Nurmasita; Sakriawati, Sakriawati; Wahyuningsih, Sri; Hansur, Lismayana; Bin Laeto, Arwan (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2024)
The final project is one of the main requirements for studenst to obtain a graduation degree. However, some students are not psychologically prepared to face it, leading to anxiety disorders. Anxiety is a state that can cause someone to feel uncomfortable, restless, afraid, worried, and uneasy, accompanied by various physical symptoms. anxiety also refers to a person's subjective feelings of tension, fear, nervousness, and worry. The high level of anxiety makes a person's normal life difficult, such as disrupting activities and social life. Anxiety is one of the various types of emotional and behavioral disorders. The purpose of this research is to determine the Description of the Anxiety Level of Final Year Students in the D-III Nursing Education Program. This research method uses Descriptive Quantitative with a population of all final-year students from the 2022 cohort at the Yapenas 21 Maros Nursing Academy campus. The research results show that the majority of respondents experienced moderate anxiety levels at 60%, students who experienced mild anxiety levels at 26.7%, and students who experienced severe anxiety levels at 13.3%. It can be concluded that the majority of final-year students from the 2022 cohort of the D-III Nursing Education program at the Yapenas 21 Maros Nursing Academy are at a moderate level when facing their final scientific writing task (KTI).